EXPLORING GENERATION X AND MILLENNIAL CONSUMER BEHAVIORS REGARDING CREATIVE ECONOMY PRODUCT PROMOTION VIA WHATSAPP IN THE SOCIETY 5.0 ERA - Nova Rianti S; Muhammad Habibi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to explore the differences in consumer behavior between Generation X and Millennials in responding to creative economy product promotions via the WhatsApp platform, using a qualitative approach based on a literature review. The main focus of this study is to conceptually examine how the characteristics of each generation influence how they respond to digital promotional messages delivered through personal communication media. The data analyzed comes from various library sources, including scientific journals, books, research reports, and recent articles related to consumer behavior, WhatsApp marketing, and the dynamics of the creative economy in the Society 5.0 era. The study results show that Millennials tend to be more responsive to visual, interactive, and fast-paced promotions, in line with their higher levels of technology adoption. Conversely, Generation X is more cautious and selective, and places great emphasis on the credibility of information sources. WhatsApp, with its direct and personal communication characteristics, has great potential as an effective digital promotional medium, especially if communication strategies are tailored to the characteristics of each generation. This research is expected to provide a conceptual contribution to the development of more targeted digital marketing strategies in the creative economy sector.